Interdisciplinary Approach for the Treatment of Complex Bilateral Cleft Lip and Palate With Missing Premaxilla. (May 2022) - Park, Yong Jong; Derderian, Christopher; Oppedisano, Michael
Complex craniofacial deformities such as complete bilateral cleft lip and palate require interdisciplinary approach for proper diagnosis and treatment. A severe skeletal discrepancy caused by bilateral cleft lip and palate and missing premaxilla was successfully managed with orthodontic preparation and distraction osteogenesis. Conventional prosthodontic treatment combined with orthodontic preparation was proven to be a viable option to manage multiple missing teeth in cleft lip and palate.